The association between animal source food intake and growth among preschool children in Jakarta - Hidayatulloh, Agus; Fahmida, Umi; Kolopaking, Risatianti; Harjatmo, Titus Priyo; Pritasari, Pritasari (World Nutrition Journal, 2025)
Background: Animal-source foods (ASF) are a source of high-quality protein and bioavailable micronutrients such as iron and zinc, which are important for the growth of preschool children. However, despite high ASF intake, malnutrition in Jakarta is above the national prevalence. The types of ASF consumed may have contributed to this. Objective: This study aims to investigate the association between ASF intake and height-for-age Z-scores (HAZ) among preschool children aged 4–6 years in Jakarta.